The Relationship of Healthy Rationalist Pundit Thinking to the Spiking and Block Performance of Volleyball For Junior Players - Maladh Hayder Ahmed; Najlaa Abas Nasef (Indian Journal of Forensic Medicine & Toxicology, 2021)
The game of volleyball is one of the competitive team games that has taken the lead in terms of its spread inthe world. The game of volleyball depends on basic skills as an important base on which this game buildsto advance in the level of performance, and among these skills is the skill of spoiling and blocking, theresearch aims to identify the extent of the relationship of critical thinking with the performance of spoilingand blocking in volleyball for junior players. The sample was chosen from volleyball players from Baghdadclubs represented (Sulaikh Club, Students Club, Army Club, Police Club, Industry Club, Al HussainiyaClub, Al Karkh Club, Frontier Club) for the 2020 season, the researchers used the descriptive approach andthe research community was composed of (101) players. The researchers prepared the pundit thinking scaleconsisting of 36 items, Percentages were calculated, the arithmetic average and hypothesis were calculated.The reliability coefficient was found using the half segmentation method and (Alpha Cronbach) to knowthe test stability and correlation coefficient (Pearson) validation discriminatory paragraph and t-test, in lightof the results of the research, conclusions were reached, where the players found critical thinking to havea positive relationship in the skills of hitting and spoiling, and the researchers also recommend conductingmore research on critical thinking skills in other variables in the game of volleyball.